Product/Business Portfolio management: Logic, structural, and managerial implications - S. Shabalala (South African Journal of Business Management, 1985)
The objective and scope of this article are to discuss the logic of Product/Business Portfolio management and to demonstrate how the expected optimal results of such management are undermined, if not completely undermined by factors which are quintessential to organization circumstances. These factors include, among other things, organizational structural attributes (differentiation, integration systems, power distribution, units inter-dependences etc.), information availability, personal values of managers, reward systems, etc. In discussing the Issues mentioned above the sequence will be as follows: The overall look at the basic concept of Product/Business Portfolio strategic management; the general limitations of the normative-rational assumptions of Strategic Business Units (SBUs) Portfolio management; the specific attention to be paid to individual organizational and managerial factors as they affect strategic management in diversified companies; and the implications of the above Issues to top management of business institutions.
Keywords: 650